STRONTIUM-BARIUM CARBONATITES OF THE MURUN MASSIF (EASTERN SIBERIA, RUSSIA) - Vorob'ev E.I. (My University, 2001)
The Murun massif is composed of a complex association of alkali, nepheline, and kalsilite syenites and includes specific carbonatites with BaO- and SrO-rich carbonates, which belong to a special type of barium-strontium carbonatite. Their other specific features are as follows: the dominance of Ba over Sr in carbonates, a pyroxene-potassic feldspar-carbonate mineral assemblage, and a spatial and genetic relation to potassic syenite massifs. The carbonate component of these rocks was primarily SrCO3 + CaCO3 + BaCO3 solid solution, which contained 25.6 wt % CaO, 10.75 wt % SrO, 31.67 wt % BaO, 0.30 wt % TR2O3, and 31.55 wt % CO2 and suffered multistage transformation with the development of exsolution textures and corresponding mineral assemblage of calcite, strontionite, and baritocalcite. The barium-strontium carbonatites crystallized from alkalic carbonate melts at the final evolutionary stage of a highly differentiated potassic syenite massif. They are located within the field of pyroxene-potassic feldspar fenites and are accompanied by pyroxene-potassic feldspar-calcite carbonatites and charoitic rocks. The carbonatite finding was predicted by analyzing the calcite composition in the associated rocks. The large Sr-Ba carbonatite body in the Murun massif is a unique deposit of new Sr-Ba carbonate ores. They are used as reagents for killing, refining, modifying, and doping the steel and cast iron to improve the structural metal strength. Mining and exploitation of these ores in ferrous metallurgy does not bring harm to environmental conditions.